Differentiation of hypointense nodules on gadoxetic acid-enhanced hepatobiliary-phase MRI using T2 enhanced spin-echo imaging with the time-reversed gradient echo sequence: An initial experience. Issue 95 (October 2017) - Yoneyama, Masami; Takayama, Yukihisa; Nishie, Akihiro; Nakamura, Masanobu; Katsumata, Yasutomo; Takemura, Atsushi; Obara, Makoto; Okuaki, Tomoyuki; Honda, Hiroshi; Van Cauteren, Marc
Highlights: T2-fast field echo (T2FFE) is a T2 weighted gradient echo sequence but also has T1 shortening effect. T2FFE in the hepatobiliary phase (HBP) of gadoxetic acid-enhanced (Gd-EOB) MRI is useful for differentiating benign and malignant liver lesions. Benign lesions showed a positive contrast whereas malignant lesions showed a negative contrast on T2FFE images in the HBP of Gd-EOB-MRI. Abstract: Purpose: To optimize the flip angle (FA) of the T2 enhanced spin-echo imaging using the time reversed gradient echo (T2FFE) and evaluate its utility for differentiating hypointensity nodules in the hepatobiliary phase (HBP) of gadoxetic acid-enhanced (Gd-EOB) MRI. Materials and methods: First, FA optimization of the T2FFE in the HBP was investigated by comparing signal-to-noise ratio (SNR) among different FAs using phantoms. The liver-to-muscle contrast ratios (CRLiver-Muscle ) and image quality among three FAs (20°, 50° and 80°) were compared using images of 10 patients. Next, the utility of the T2FFE with an optimized FA for differentiating hypointensity nodules in the HBP was assessed by comparing the lesion-to-liver contrast ratio (CRLesion-Liver ) among cysts, hemangiomas, hepatocellular carcinomas, and metastatic tumors in 32 patients. Results: SNR increased as FA increased, but leveled off at FAs of 50° and greater. The FA of 50° showed significantly better image quality scores than that of 80° (p < 0.05). After employing an FA of 50°, the CRLesion-Liver value indicated that the T2FFE depicted benign lesions as hyperintense and most malignant lesions as hypointense in relation with the liver parenchyma (p < 0.05). Conclusion: The T2FFE in the HBP of Gd-EOB-MRI is useful for differentiating benign and malignant liver lesions.